Childhood vitiligo: A clinicoepidemiological study - Mrinal Gupta (Wolters Kluwer Medknow Publications, 2018)
Background: Vitiligo is a chronic disorder of pigmentation which has serious psychosocial implications. Early onset or childhood vitiligo, although clinically similar to adult-onset vitiligo, has been found to have a distinct epidemiological, clinical, therapeutic, and prognostic profile. Aims and Objectives: This study was carried out to study the clinicoepidemiological characteristics of vitiligo in patients aged <18 years. Materials and Methods: It was a prospective, observational study carried out over a period of 1 year in which fifty children having vitiligo were examined. After taking an informed consent from the attendants/parents of the patients, a complete history including age, sex, duration of the disease, family history, history of Koebner's phenomenon, and history of associated diseases was noted. Results: The study group comprised of 29 females and 21 males (male:female 1:1.38), aged between 6 months and 17 years with a mean age of 8.45 ± 2.34 years and the mean age of onset was 5.6 years. The most common clinical subtypes observed in childhood vitiligo were vitiligo vulgaris in 42% (n = 21) followed by focal in 24% (n = 12), segmental in 12% (n = 6), and acrofacial in 10% patients (n = 5). A family history of vitiligo was seen in 16% patients (n = 8). Leukotrichia was observed in four patients, Koebner phenomenon in 5, and halo nevus in one patient. Conclusions: Childhood vitiligo is a common entity with vitiligo vulgaris being the most common subtype and lower limbs being the most common site of involvement. Children with positive family history had an earlier age of onset, and thyroid abnormalities were more common in nonsegmental variant.